Complementary Phenomena: Phantom Hand and Phantom Face. Issue 2 (2nd June 2021) - Uysal, Hilmi; Şavkliyildiz, Ayhan; Özkan, Özlenen; Çolak, Ömer H.; Barçin, Ebru; Şenol, Utku; Göztepe, Mehmet Berke; Özkan, Ömer
Abstract : After tissue or limb loss, the development of sensation and perception of the lost or deafferent tissue is defined as a phantom phenomenon. We investigated the presence of phantom phenomena in individuals who underwent a full face transplant as well as those who had a hand transplant. Specifically, we investigated sensory perception of the face on the fingers and sensory perception of the fingers on the face in three full face and four hand transplant patients. In all seven individuals, we used a brush to separately stimulate the right and left sides of the face or the palmar and dorsal faces of the hand. We then asked the individuals if they felt a sensation of touch on any other part of their body and, if so, to describe their perceptions. Changes in the regions of the primary sensory cortex representing the hand and face were defined using fMRI obtained via tactile sensory stimulation of the clinical examination areas. Two of the full face transplant patients reported sensory perceptions such as a prominent sensation of touch on their faces during sensory stimulation of their fingers. Three of the hand transplant patients reported sensory perceptions, which we referred to as finger patches, during sensory stimulation of the face area. In fMRI, overlaps were observed in the cortical hand and face representation areas. We consider the phantom hand and phantom face phenomena we observed to be complementary due to the neighborhood of the representations of the hand and face in the somatosensory cortex.